Effect of shading on milk production and quality in Girolando cows - Teixeira, Pamella Cristina; Carmo, Ruthele Moraes do; Leão, Paulo Víctor Toledo; Cunha, João Vítor Teixeira da; Silva, Esther Cristina Neves Medeiros da; Gadêlha, Stefany Cristiny Ferreira da Silva; Santana, Clistiane Santos; Pereira, Gustavo Machado; Cordeiro, Clarice Gebara Muraro Serrate; Costa, Adriano Carvalho; Paim, Tiago do Prado; da Silva, Marco Antônio Pereira (Food Science and Technology, 2025)
The aim of this study was to evaluate the effect of shading on milk production and milk quality in Girolando cows. A total of 16 Girolando cows were used, divided into two groups for two treatments: the first group remained in a paddock without shade and the second in a paddock with shade. Every 15 days, each group of animals underwent one of the treatments, totaling 120 days of experiment. The 15 days of permanence in each treatment was divided into two periods: 7 days for adaptation and 8 days for sample collection. During the period of data collection, the following variables were measured: the temperature and relative humidity of the air in the paddocks and the milking room; evaluation of the temperature and humidity index; respiratory rate and rectal and superficial temperatures of the skin and udder of the animals; and digital infrared thermographic imaging. Additionally, milk samples were collected for physicochemical evaluation and weighed to assess the daily production of the animals. Descriptive evaluations of the behavior of the animals were carried out, aiming to evaluate the thermal comfort. A cross-over experimental design was used, with an interval between the two treatments. Subsequently, analysis of variance, Pearson’s correlation, and principal component analysis were performed, and the thermographic images were processed in FLIR Tools software to ensure greater precision in relation to surface temperatures. The period of the year during which the animals are kept in sun and shade can affect the average, maximum, and minimum temperatures, the surface temperature of the skin, as well as the temperature and humidity index. It is concluded that, in animals that were subjected to both shaded and unshaded areas, there were correlations among milk constituents and between physiological and environmental variables, without any effect on milk production.